Biotechnology and Bioengineering: Volume 110, Number 11, November 2013. Issue 11 (21st September 2013) - Unknown
<x xml:space="preserve">Abstract</x> Cover Legend The cover image illustrates an alternative antibody harvest process that incorporates flocculation using a novel stimulus responsive polymer, shown here bound to cells and cell debris, aggregates, host cell proteins, and DNA. (Image courtesy of Lisa Armstrong, courtesy of Yun Kang, James Hamzik and Michael Felo et al.) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>